REPERCUSSION OF 2007- NEW CURRICULUM IN ACHIEVEMENT OF GCE (O/L) SCIENCE EXAMINATION IN BATTICALOA DISTRICT - Gnanaretnam, K (PEOPLE: International Journal of Social Sciences, 2017)
Three national examinations are conducted in Sri Lankan formal education. They are GCE (O/L), GCE (A/L), and Grade 5 scholarship examination. The achievement of GCE (O/L) is paramount important for getting small scale employment opportunities, enrolling at Technical College, and for being qualified for GCE (A/L) class. Nonetheless, the statistics witnessed that the performance of GCE (O/L) is not satisfactory. Only 60% of those who sat for GCE (O/L) are qualified for studying at GCE (A/L) class and five percent of them fail in all the subjects. Only 50 % of candidates got passes in science subject. With an aim to improve this situation, the new curriculum was introduced in 2007 in Sri Lanka. This curriculum consisted of skill development and improvement of achievements of students. It also emphasized, group discussion, and changes in lesson planning and instruction by using new 5 E model to achieve required competency level. As six years passed after the introduction of new curriculum. It is the time to appraise the repercussion of the new curriculum in the achievement level of GCE (O/L) examination. The study was conducted by using survey method in the district of Batticaloa. Both the quantitative and qualitative data were used. The study revealed that the percentage of failure in the subject of science was increased. This trend co-related with in all the other districts of the island. It is also revealed that the mean of the subject of science in GCE (O/L) at national level was also increased. This study included some suggestions to further improve the achievement of the students in the subject of science in GCE (O/L) examinations.